Analysis of Home-based Business Development Using a Green Business Approach to Increase Family Income - Munir, Miftahul; Srikalimah, Srikalimah (Politeknik Ganesha Medan, 2024)
The development of home-based businesses using a green business approach is still rare due to a lack of understanding of the importance of environmental preservation and insufficient skills in processing natural resources. Home-based products using a green business approach involve businesses that prioritize environmental considerations from the selection of raw materials and production processes to creating products that do not harm the environment. In other words, the raw materials used are natural waste products that are processed and utilized to create economic value and increase family income. The purpose of this research is to examine the development of home-based green businesses in Gembleb and their impact on income levels. The researcher used qualitative methods, directly engaging in field observations and interviews with business owners. The results of this study show that developing environmentally friendly home-based businesses by utilizing natural raw materials can generate income for families and communities. However, protecting wildlife is not solely the responsibility of individual business owners but a shared responsibility for the benefit of both individuals and groups.